2019
DOI: 10.26451/abc.06.04.13.2019
|View full text |Cite
|
Sign up to set email alerts
|

Using natural ecology to predict higher cognition in human and non-human primates

Abstract: Many critical aspects of contemporary human cognitive functionality (e.g., reading, fixing a car) evolved historically in a time frame that biological natural selection cannot account for. Because of this, the best way to understand the factors that may have led to human cognition evolution is to look at cognitive processes in nonhuman primates. I argue here that comparative approaches are successful in informing us about human cognitive evolution. Furthermore, making predictions based on natural ecology will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(88 reference statements)
0
4
1
Order By: Relevance
“…The current results raise the difficult question of interspecies differences and whether the latter could be explained by different cognitive toolboxes and/or different socioecology [60]. The ability of chimpanzees and orangutans to combine facts and abstractions in this study contrasts with the simplicity of the responses of bonobos and capuchins, which used simpler decision rules.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The current results raise the difficult question of interspecies differences and whether the latter could be explained by different cognitive toolboxes and/or different socioecology [60]. The ability of chimpanzees and orangutans to combine facts and abstractions in this study contrasts with the simplicity of the responses of bonobos and capuchins, which used simpler decision rules.…”
Section: Discussioncontrasting
confidence: 55%
“…a behaviour that is very much like that of capuchins. One possibility is that responses here are not connected to their cognitive abilities but rather to the more general difficulty bonobos have dealing with risk and ambiguity in comparison to chimpanzees, which could be linked to the feeding ecology of each species [24,40,60]. However, both species exhibited similar ambiguity aversion when compared in an ambiguous gambling game where they had no information about the odds [24].…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, Clayton and Dickinson (1999) showed a pattern of memory not seen in other birds that demonstrated that they could retrieve what occurred where and when that occurred. We have argued elsewhere how important it is to apply principles of foraging ecology to primate cognition (see Platt et al, 1996, for such an example;Schwartz, 2019). We also think that such principles would also be useful in studying human cognition (see Tooby & Cosmides, 2016, but also see Hampton, 2019).…”
Section: Ecological Approaches To Primate Cognitionmentioning
confidence: 96%
“…In addition to the importance of balancing lab work with field work, even within studies that are exclusively lab-based (or completely field-based), it is important to consider the natural ecology of any species when considering their cognition (Schwartz, 2019). Ecological considerations as simple as whether an animal can or cannot use its fingers to press icons on a touchscreen can impact the possible outcomes for a study.…”
Section: Ecological Approaches To Primate Cognitionmentioning
confidence: 99%
“…A more diverse feeder such as golden-lion tamarin (Leontopithecus rosalia) will need to search a much wider landscape to obtain food. Thus, Platt et al showed that such foraging ecology influences their cognitive strengths (see Schwartz, 2019). Similarly, Menzel and Sayers (2022) reviewed the literature on spatial cognition and how differences in the use of space by related New World monkey species predicts the monkeys' performance across a number of spatial tasks.…”
Section: The Natural Selection Of Metacognitionmentioning
confidence: 99%